1991
DOI: 10.1016/0014-5793(91)80122-j
|View full text |Cite
|
Sign up to set email alerts
|

Examination of elongation factor Tu for aluminum fluoride binding sites using fluorescence and 19F‐NMR methodologies

Abstract: This art)tic reports on a companion of the tl,ller~clion tf AP' and F with two GTP.hindmg proteins, clonga;ion factor T-(~F-To} ~nd the humtune scnsllWC regulatory protein ((3 protein) O.z The racthodolo$1¢x tbotcn to elucidate i~ssihle interactions hot.ten protein and alumplum fluoride were Iluor¢~:en~e ~r~clro~:opy and nuclear raagn¢tl¢ r<,~onan¢¢ ()"F.NM R) Bolh prottm~ have tryptoph~n residues near their nucleolide bindlnl| ~lte~, the pu~orted s)t¢ of aluminum fluoride inter~¢lloll It hal bccn assumed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…No change is observed in the HMQC spectrum, and so aluminum fluoride is probably not a good transitionstate analogue for EFTu (data not shown). The same conclusion was also reached by Hazlett et al (1991) 12 11 1H (PPM) figure 6: Selective 15N difference decoupling of the downfield resonances as indicated, from fully 15N-labeled EFTu complexed with Mn2+. Neither downfield glycine resonance (A and C) is significantly perturbed by the Mn2+.…”
Section: Resultssupporting
confidence: 68%
“…No change is observed in the HMQC spectrum, and so aluminum fluoride is probably not a good transitionstate analogue for EFTu (data not shown). The same conclusion was also reached by Hazlett et al (1991) 12 11 1H (PPM) figure 6: Selective 15N difference decoupling of the downfield resonances as indicated, from fully 15N-labeled EFTu complexed with Mn2+. Neither downfield glycine resonance (A and C) is significantly perturbed by the Mn2+.…”
Section: Resultssupporting
confidence: 68%
“…Such fluorescent analogs are sensitive to changes in the local structure of the protein (13,14). Even with 5 pM RasmGDP and excess A1F4-, there was little or no change (<3%) of fluorescence (12,15). It has been proposed that the role of GAP might be to stabilize or induce the formation of a transition state in the GTPase reaction (16), and that GAP supplies the helical domain or similar structure that exists in G a proteins (4) and is necessary for GTP hydrolysis (17).…”
mentioning
confidence: 99%
“…Sternweis and Gilman (1982) first reported that fluoride in the presence of aluminum could stimulate the guanine nucleotide-dependent activation of adenylate cyclase in partially purified cyc-S49 cell membranes. AlF4-has been proposed to be the active species required for this activation and is believed to mimic the y-PO4 ion of GTP and bind to GDP-bound G proteins, thus leading to dissociation of the active cy subunit (Bigay et al, 1987;Hazlett et al, 1991). AlF4-has been used extensively to assess whether G proteins are involved in a variety of cellular processes.…”
Section: Discussionmentioning
confidence: 99%